Agricultural Use of Biosolids Generated in Wastewater Treatment of a Food Industry (2020)
Biosolids generated as waste from a Wastewater Treatment Plant (WTP) are a pollution problem by the provision of large volumes in landfills and the waste of their potential as an agricultural input.  The research conducted trials to analyze the agricultural use of biosolids in a food company's WTP, their effects on the germination and development of the vegetal plant species Coriandrum sativum were assessed through trials that mixed different amounts of biosolids, land soil and commercial fertilizer, and took into account: planting site characteristics, biosolid and Coriandrum sativum. A random block design was made to compare treatments understudy and resulted in the combination of 50% biosolids with 50% land soil was the best test by germination, height, mass and length of the roots of the plant studied.  In the evaluation of results, the behavior of dependent variables was analyzed: germination, height, mass and length with respect to the four test types with their respective repetitions using ANOVA and Fisher's significant minimum difference (LSD) to determine the effect the biosolid had on the plant and to know the optimal dose for its development.  The germination rate (GR) was also determined in the trials, and 98.3% was found for the best treatment indicating that the substrate does not contain phytotoxic elements.